Radiographic joint destruction in postmenopausal rheumatoid arthritis is strongly associated with generalised osteoporosis. Issue 7 (1st July 2003) - Forsblad d'Elia, H; Larsen, A; Waltbrand, E; Kvist, G; Mellström, D; Saxne, T; Ohlsson, C; Nordborg, E; Carlsten, H
Abstract : Objectives: To investigate determinants of joint destruction and reduced bone mineral density (BMD) in postmenopausal women with active rheumatoid arthritis (RA) not treated with bisphosphonates or hormone replacement therapy and to evaluate if there are common markers of erosive disease and bone loss. Methods: BMD was measured using dual x ray absorptiometry and joint damage was examined by x ray examination according to the Larsen method in 88 patients with RA. Associations between BMD and Larsen score, and between demographic and disease related variables, including proinflammatory cytokines, HLA-DR4 epitopes, and markers of bone and cartilage turnover, were examined bivariately by simple and multiple linear regression analyses. Results: 49/88 (56%) patients had osteoporosis in at least one site. Reduced BMD and increased joint destruction were associated with: at the forearm and femoral neck, high Larsen score, low weight, and old age ( R 2 =0.381, p<0.001; R 2 =0.372, p<0.001, respectively); at the total hip, low weight, high Larsen score, and dose of injected glucocorticosteroids ( R 2 =0.435, p<0.001); at the lumbar spine, low weight, reduced cartilage oligomeric matrix protein, and increased carboxyterminal propeptide of type I procollagen ( R 2 =0.248, p<0.001). Larsen score was associated with long disease duration and increased C reactive protein (CRP) ( R 2 =0.545, p<0.001). Conclusions: Osteoporosis is common in postmenopausal patients with RA. Low weight and high Larsen score were strongly associated with BMD reduction. Increased CRP and long disease duration were determinants of erosive disease in postmenopausal women with RA. These findings indicate common mechanisms of local and generalised bone loss in RA.